SOME DATABASE MANAGEMENT TOOLS FOR DATA MODELING AND REVERSE ENGINEERING - Adrian RUNCEANU; Marian Ion POPESCU (Fiabilitate şi Durabilitate)
In this paper we tested the design of a database using database management tools. We compared some existing software products highlighting the platforms they can run on, the types of integrated databases, specific features, advantages and disadvantages. The implementation was done in PostgresSQL 15, and for the database schema we used Altova's DatabaseSPY utility.